Resilient Ecosystems: Key to Environmental Disaster Resilience and Logistics Efficiency - Djohar; Dety Junita (Jurnal Penelitian Pendidikan IPA, 2025)
One sector that is significantly affected is the logistics sector. Disruptions to transportation infrastructure, communication networks, and supply chains can hamper the distribution of humanitarian aid, evacuation of victims, and post-disaster economic recovery. This research was conducted in Gowa Regency, from the Gowa Regency disaster incident that occurred from 15-25 December 2024, and January 2025. Strong winds and landslides caused damage to residents' houses, agricultural land, and road infrastructure. The purpose of this study is to examine Resilient Ecosystems: Key to Environmental Disaster Resilience and Logistics Efficiency. Descriptive research methods aim to provide a clear and detailed picture of a phenomenon, event, or characteristic of a particular population.  The results of this study explain: The function of the ecosystem is as a habitat for living things; as a natural resource; as a regulator of environmental balance; as a place of protection; oxygen production; carbon dioxide absorption; climate regulation; erosion prevention; pollination; pest and disease control; provision of clean water: the role of resilient ecosystems in environmental disaster resilience: disaster risk reduction; coastal protection; climate regulation; provision of resources; ecosystem restoration: several efforts to build resilient ecosystems: biodiversity conservation; ecosystem restoration; sustainable resource management; reduction of greenhouse gas emissions; increasing public awareness.